Early Asiatic migration to the Americas : A view from South America - Politis, Gustavo Gabriel (2015)
Fil: Politis, Gustavo Gabriel. División Arqueología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina